An Analytical Framework for Predicting the Limit in Structural Refinement in Accumulative Roll Bonded Nickel - Duan, J.; Quadir, Md Zakaria; Ferry, M. (2015)
The limit in structural refinement of lamellar bands (LBs) generated during accumulative roll bonding (ARB) of commercially pure nickel was investigated by transmission electron microscopy and transmission Kikuchi diffraction. A typical LB consists of an internal cellular substructure of low angle boundaries (LABs) bounded by two high angle boundaries (HABs) that are aligned parallel to the rolling plane. At low true strains (e < 2.4; 1 to 3 ARB cycles), the deformation substructure was distributed heterogeneously; nano-sized (~80 nm) equiaxed grains containing mainly HABs were generated in the vicinity of the roll bonding region of the individual nickel layers, whereas a typical dislocation substructure containing LABs was generated in their interior. At high strains (e > 4.8; 6 to 10 ARB cycles), a homogenous distribution of well-defined, highly elongated LBs of average thickness 75 nm was generated throughout the entire thickness of the material. The thickness of these LBs decreased with increasing number of ARB cycles and reached a saturation thickness of ~75 nm after 6 to 8 cycles. A theoretical framework for the limit to LB refinement during ARB is presented based on the refinement rate due to the stored energy of deformation balanced by the growth rate caused by adiabatic heating. The analysis takes into account the unique features of LB structures and processing parameters.